2005
DOI: 10.1108/14777830510614349
|View full text |Cite
|
Sign up to set email alerts
|

Changing corporate attitudes towards environmental policy

Abstract: PurposeTo report findings from an updated survey of environmental policy and practice among UK organizations. To draw conclusions about the relationship between environmental concerns and organizational strategy making.Design/methodology/approachThe paper reports findings from a 1999 survey of 911 UK organizations, updated by interviews conducted with participant organizations in 2004. The paper represents an extension of a ten‐year longitudinal study of environmental policy and practice in UK organizations.Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
3
19
0
2
Order By: Relevance
“…The greater the emphasis of top management to embed good environmental practice and ethics structurally and culturally into their organizations, the better the rate of success in the adoption of the environmental programme, due to the commitment and work culture that result from it (Faulkner, Carlisle, & Viney, 2005;Kasim, 2007;Stone et al, 2004). Conversely, when commitment of top management is detached and uncaring, falters, lacks understanding between environmental and economic cost relationship and does not regard environment as a key value, it could pose a potential barrier to an organization's initiatives in the implementation of environmentally friendly practices (Post & Altman, 1994).…”
Section: Top Managementmentioning
confidence: 99%
“…The greater the emphasis of top management to embed good environmental practice and ethics structurally and culturally into their organizations, the better the rate of success in the adoption of the environmental programme, due to the commitment and work culture that result from it (Faulkner, Carlisle, & Viney, 2005;Kasim, 2007;Stone et al, 2004). Conversely, when commitment of top management is detached and uncaring, falters, lacks understanding between environmental and economic cost relationship and does not regard environment as a key value, it could pose a potential barrier to an organization's initiatives in the implementation of environmentally friendly practices (Post & Altman, 1994).…”
Section: Top Managementmentioning
confidence: 99%
“…Evidence of competitive and legitimation pressures on corporate environmental decision-making was also seen in Delmas and Toffel"s (2008) study and a series of surveys conducted on UK firms as detailed in Ghobadian et al (1998), James et al (1999) and Faulkner, Carlisle and Viney (2005). It was found that organisations "adopt distinct sets of management practices that appease different external constituents" (Delmas & Toffel 2008, p. 1027.…”
Section: Motivational Factorsmentioning
confidence: 88%
“…The questionnaire was mostly developed by adapting existing literature in corporate environmental sustainability including studies by Delmas and Toffel (2008), Hahn and Scheermesser (2006), and a longitudinal series of studies from the UK (Faulkner, Carlisle & Viney 2005;Ghobadian et al 1998;James et al 1999). To measure the extent of green IT within an organisation, a self-reported six measure score was developed from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The study found that organizations are still primarily focused on short-term issues even though they appreciate the opportunities offered by adopting environmentally sustainable practices (Faulkner, Carlisle, & Viney, 2005). A 1999 survey of 911 organizations in the United Kingdom, updated by interviews in 2004, reveals that environmental concerns have not yet become part of the key strategy-making process in many firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%